DETECTIVE REALITY AND INDIVIDUAL INTERPRETATION - Kholikov Bakhodir Alikulovich (IAIN MADURA, 2016)
The article presents scientific analytical conclusions on the established opinions about literary-theoretical views related to the literary life, psychology of creativity, writer’s skillfulness, spiritual-educational world of a person in fiction as a result of special studies of the close and analogical literary phenomena in fiction writing. On the material of the novel “Godfather” by a prominent American writer of the XXth century Mario Puzo and “Shaytanat” (“Band of Devils”) by Uzbek writer Tokhir Malik, the society’s stability and negative factors influencing social-spiritual life of the society are analyzed.